Leadership, capacity building, and school improvement concepts, themes, and impact - Dimmock, Clive A. J. (Oxon [England] : Routledge, an imprint of Taylor & Francis Group, 2012)
"The Leadership for Learning series explores the connections between educational leadership, policy, curriculum, human resources and accountability. Each book in the series approaches its subject matter through a three-fold structure of process, themes and impact. Series Editors - Clive Dimmock, Mark Brundrett and Les Bell Leadership,"-- Provided by publisher.
pt. 1. Conceptualizing and contextualizing leadership -- pt. 2. Contemporary leadership themes -- pt. 3. Policy, leadership practice and impact.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: School management and organization; Educational leadership; School improvement programs; Electronic books